Colonic neuropathology is not associated with autonomic dysfunction in Parkinson's disease. (April 2019) - Leclair-Visonneau, Laurène; Clairembault, Thomas; Volteau, Christelle; Chapelet, Guillaume; Le Dily, Séverine; Vavasseur, Fabienne; Coron, Emmanuel; Préterre, Cécile; Neunlist, Michel; Péréon, Yann; Derkinderen, Pascal
Abstract: Introduction: Dysautonomia in Parkinson's disease (PD) has been shown to be associated with disease severity and especially with the occurrence of dementia. One proposed explanation for this finding is that phosphorylated alpha-synuclein histopathology (PASH), the characteristic pathological feature of PD is more diffuse in dysautonomia-associated PD than in disease without dysautonomia, not only in the central nervous system but also in peripheral autonomic networks. The aim of this study was therefore to determine if colonic alpha-synuclein histopathology is associated with dysautonomia in PD. Methods: A total of 43 PD patients participated in this study. For each patient, two biopsies were taken in the sigmoid colon and analyzed by immunohistochemistry with antibodies against phosphorylated alpha-synuclein and PGP 9.5. All patients had a complete neuropsychological and neurological assessment along with a comprehensive evaluation of dysautonomia with questionnaires (SCOPA-Aut, NMS-Quest, Rome III constipation criteria and dry eye symptoms) and functional tests (pupillometry, Saxon and Schirmer's tests, heart rate variability, orthostatic blood pressure measure and sympathetic skin response). Results: Colonic PASH was observed in 20/43 PD patients. No differences were observed in autonomic symptoms and testing between patients with and without PASH. Conclusions: Although frequent in PD, autonomic dysfunction is not related to colonic PASH. In addition to the existing literature, our findings further suggest that each dysautonomic symptom in PD might not be associated with a more severe or diffuse PASH not only in the central nervous system but also in the peripheral autonomic nervous systems. Highlights: 47% of PD patients exhibited alpha-synuclein neuropathology in the sigmoid colon. There was no association between colonic neuropathology and dysautonomia. Dysautonomia in PD might not be associated with a more diffuse alpha-synuclein pathology.